Application of repetitive language style in the text of the form 4 novel of Lieutenant Adnan by Abdul Latip Talib - Shauqi, Muhammad Ameer; Mokhtar, Marzni Mohamed; Ahmadi, Muhammad Aiman Syazwan; Abdullah, Muhammad Ikhwan Danial (University of Malaya, 2024)
This study aims to explore the application of the repetitive language style found in the novel Lieutenant Adnan by Abdul Latip Talib. The first objective of this study is to identify the application of repetition language style which includes six different types namely anaphora, epiphora, simplok, response, woordopname and parallelism. The second is to identify the application of the most dominant repetitive language style found in the text of this novel. The research methodology involves qualitative research based on text analysis of Lieutenant Adnan's novel by Abdul Latip Talib. This study uses Stylistic Theory based on the views of J.J Webber (1989). The analysis of this study also involves close and careful reading of each word, phrase and sentence to identify the application of repetitive language style found in the text of this novel. The results of the study found that the application of repetitive language style consists of anaphora, epiphora, simplok, response, woordopname and parallelism. The analysis found that the author uses this repetitive language style to emphasize and develop ideas in his writing sentences. In addition, the author of this novel likes to use the language style of anaphora repetition in his writing. The impact is that the application of language style elements in the writing of a novel text is seen to be able to act as an intermediary between the author and the reader to convey thoughts or ideas to be perceived and appreciated more easily and meaningfully in addition to enriching the aesthetic value of language in the writing of a novel text.